At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Connect with a community of experts ready to provide precise solutions to your questions quickly and accurately. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Let's solve and simplify the given expressions step by step.
1. First Expression:
We need to multiply and simplify:
[tex]\[ (\sqrt{x} - 2\sqrt{2})(\sqrt{x} + 2\sqrt{2}) \][/tex]
This expression is in the form of a difference of squares:
[tex]\[ (a - b)(a + b) = a^2 - b^2 \][/tex]
where [tex]\( a = \sqrt{x} \)[/tex] and [tex]\( b = 2\sqrt{2} \)[/tex].
Applying the formula:
[tex]\[ (\sqrt{x} - 2\sqrt{2})(\sqrt{x} + 2\sqrt{2}) = (\sqrt{x})^2 - (2\sqrt{2})^2 \][/tex]
Simplify each term:
[tex]\[ (\sqrt{x})^2 = x \][/tex]
[tex]\[ (2\sqrt{2})^2 = 4 \cdot 2 = 8 \][/tex]
So the expression simplifies to:
[tex]\[ x - 8 \][/tex]
2. Second Expression:
Next, we need to simplify:
[tex]\[ (\sqrt{x} - \sqrt{2})^2 \][/tex]
This is a binomial squared, which can be expanded using the formula:
[tex]\[ (a - b)^2 = a^2 - 2ab + b^2 \][/tex]
where [tex]\( a = \sqrt{x} \)[/tex] and [tex]\( b = \sqrt{2} \)[/tex].
Applying the formula:
[tex]\[ (\sqrt{x} - \sqrt{2})^2 = (\sqrt{x})^2 - 2(\sqrt{x})(\sqrt{2}) + (\sqrt{2})^2 \][/tex]
Simplify each term:
[tex]\[ (\sqrt{x})^2 = x \][/tex]
[tex]\[ (\sqrt{2})^2 = 2 \][/tex]
[tex]\[ 2(\sqrt{x})(\sqrt{2}) = 2\sqrt{2x} \][/tex]
Combining these, we get:
[tex]\[ (\sqrt{x} - \sqrt{2})^2 = x - 2\sqrt{2x} + 2 \][/tex]
Therefore, the simplified forms of the expressions are:
[tex]\[ (\sqrt{x} - 2\sqrt{2})(\sqrt{x} + 2\sqrt{2}) = x - 8 \][/tex]
and
[tex]\[ (\sqrt{x} - \sqrt{2})^2 = x - 2\sqrt{2x} + 2 \][/tex]
Thus, the filled square in the final result box would be:
[tex]\[ (\sqrt{x}-\sqrt{2})^2 = x - 2\sqrt{2x} + 2 \][/tex]
1. First Expression:
We need to multiply and simplify:
[tex]\[ (\sqrt{x} - 2\sqrt{2})(\sqrt{x} + 2\sqrt{2}) \][/tex]
This expression is in the form of a difference of squares:
[tex]\[ (a - b)(a + b) = a^2 - b^2 \][/tex]
where [tex]\( a = \sqrt{x} \)[/tex] and [tex]\( b = 2\sqrt{2} \)[/tex].
Applying the formula:
[tex]\[ (\sqrt{x} - 2\sqrt{2})(\sqrt{x} + 2\sqrt{2}) = (\sqrt{x})^2 - (2\sqrt{2})^2 \][/tex]
Simplify each term:
[tex]\[ (\sqrt{x})^2 = x \][/tex]
[tex]\[ (2\sqrt{2})^2 = 4 \cdot 2 = 8 \][/tex]
So the expression simplifies to:
[tex]\[ x - 8 \][/tex]
2. Second Expression:
Next, we need to simplify:
[tex]\[ (\sqrt{x} - \sqrt{2})^2 \][/tex]
This is a binomial squared, which can be expanded using the formula:
[tex]\[ (a - b)^2 = a^2 - 2ab + b^2 \][/tex]
where [tex]\( a = \sqrt{x} \)[/tex] and [tex]\( b = \sqrt{2} \)[/tex].
Applying the formula:
[tex]\[ (\sqrt{x} - \sqrt{2})^2 = (\sqrt{x})^2 - 2(\sqrt{x})(\sqrt{2}) + (\sqrt{2})^2 \][/tex]
Simplify each term:
[tex]\[ (\sqrt{x})^2 = x \][/tex]
[tex]\[ (\sqrt{2})^2 = 2 \][/tex]
[tex]\[ 2(\sqrt{x})(\sqrt{2}) = 2\sqrt{2x} \][/tex]
Combining these, we get:
[tex]\[ (\sqrt{x} - \sqrt{2})^2 = x - 2\sqrt{2x} + 2 \][/tex]
Therefore, the simplified forms of the expressions are:
[tex]\[ (\sqrt{x} - 2\sqrt{2})(\sqrt{x} + 2\sqrt{2}) = x - 8 \][/tex]
and
[tex]\[ (\sqrt{x} - \sqrt{2})^2 = x - 2\sqrt{2x} + 2 \][/tex]
Thus, the filled square in the final result box would be:
[tex]\[ (\sqrt{x}-\sqrt{2})^2 = x - 2\sqrt{2x} + 2 \][/tex]
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.